2021
DOI: 10.5194/bg-18-5423-2021
|View full text |Cite
|
Sign up to set email alerts
|

Impact of dust addition on the metabolism of Mediterranean plankton communities and carbon export under present and future conditions of pH and temperature

Abstract: Abstract. Although atmospheric dust fluxes from arid as well as human-impacted areas represent a significant source of nutrients to surface waters of the Mediterranean Sea, studies focusing on the evolution of the metabolic balance of the plankton community following a dust deposition event are scarce, and none were conducted in the context of projected future levels of temperature and pH. Moreover, most of the experiments took place in coastal areas. In the framework of the PEACETIME project, three dust-addit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 96 publications
2
11
0
Order By: Relevance
“…During an artificial in situ DIP enrichment experiment in the eastern Mediterranean, P rapidly circulated through hprok and heterotrophic ciliates, and the phytoplankton were not directly linked to this "bypass" process . Bioassays conducted in the tropical Atlantic Ocean have also shown that hprok respond more strongly than phytoplankton to nutrients from Saharan aerosols (Marañón et al, 2010), a pattern that has been confirmed in a meta-analysis of dust addition experiments (Guieu et al, 2014a;Guieu and Ridame, 2021;Gazeau et al, 2021). We considered hprokN demand together with phytoN demand and compared it to autochthonous (DON hydrolysis by ectoenzymatic activity) and allochthonous (atmospheric deposition) sources.…”
Section: A Snapshot Of Biological Fluxes In the ML And Their Link To New Din From Atmospheric Dry Depositionmentioning
confidence: 79%
See 4 more Smart Citations
“…During an artificial in situ DIP enrichment experiment in the eastern Mediterranean, P rapidly circulated through hprok and heterotrophic ciliates, and the phytoplankton were not directly linked to this "bypass" process . Bioassays conducted in the tropical Atlantic Ocean have also shown that hprok respond more strongly than phytoplankton to nutrients from Saharan aerosols (Marañón et al, 2010), a pattern that has been confirmed in a meta-analysis of dust addition experiments (Guieu et al, 2014a;Guieu and Ridame, 2021;Gazeau et al, 2021). We considered hprokN demand together with phytoN demand and compared it to autochthonous (DON hydrolysis by ectoenzymatic activity) and allochthonous (atmospheric deposition) sources.…”
Section: A Snapshot Of Biological Fluxes In the ML And Their Link To New Din From Atmospheric Dry Depositionmentioning
confidence: 79%
“…Based on these we used a mean C/P of 130 for phytoplankton. A C/P value of 100 was used for heterotrophic prokaryotes (Godwin and Cotner, 2015).…”
Section: Budget From the Metabolic Fluxesmentioning
confidence: 99%
See 3 more Smart Citations